A Study of the Effect of Starch Content on the Water Absorption of PVA/starch Blends - Bushra H. Musa; Nahida J. Hameed (Engineering and Technology Journal, 2021)
The present work aims to study physical tests such as the water absorption tests of PVA; PVA/corn starch blends at different mass percent (25, 30, 35, 40, and 50%) of corn starch after immersion in distilled water for ten minutes. The blends were also characterized by FTIR analysis, and an optical microscope. Casting method used to prepare samples. The results of water absorption exhibited that the weight losses of the sample increases the starch content rises in the PVA matrix. Also, it was found the highest value of the swelling ratio % at (50% PVA /50% Starch) blend, while minimum values of the swelling ratio % at (75%PVA /25%Starch) blend and pure PVA film. It was observed from optical microscope that the starch granules disperse well at 25 and 30 wt.% of the starch in the blend films. Nevertheless, clustering could be observed in the polymer blend at 35, 40, and 50 wt.% of starch component. It was shown that porous and spherical voids after the samples were immersed in distilled water.